2002
DOI: 10.1023/a:1023949707669
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Light- and dark-adaptation leads to changes in rhabdom morphology and photopigment distribution in the octopus retina. Molecular chaperones, including heat shock proteins (Hsps), may be involved in specific signaling pathways that cause changes in photoreceptor actin- and tubulin-based cytoskeletons and movement of the photopigments, rhodopsin and retinochrome. In this study, we used immunoblotting, in situ RT-PCR, immunofluorescence and confocal microscopy to localize the inducible form of Hsp70 and the large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…However, only HSC70 and Hsp86 were also found in the mature retina of rats. Others have also found Hsp70 in animal studies [4749] just as Hsp40 [47] and Hsp90 [48] have been previously observed (Table 1). …”
Section: Heat Shock Proteins In the Normal Eyesupporting
confidence: 72%
“…However, only HSC70 and Hsp86 were also found in the mature retina of rats. Others have also found Hsp70 in animal studies [4749] just as Hsp40 [47] and Hsp90 [48] have been previously observed (Table 1). …”
Section: Heat Shock Proteins In the Normal Eyesupporting
confidence: 72%
“…They also play key roles in the maturation of signal transduction proteins, such as hormone receptors, protein kinases, and nitric oxide synthase, by forming specific complexes (Csermely et al 1998;Garcia-Cardena et al 1998;Imai and Yahara 2000;Richter and Buchner 2001). Although more than 100 genes belonging to the HSP90 family exist in various organisms (Chen et al 2006), little is known about HSP90 genes in mollusks (Tomanek and Somero 1999;Ochoa et al 2002;Farcy et al 2007;Gao et al 2007). To the best of our knowledge, full-length complementary DNA (cDNA) sequences of HSP90s have been cloned from only five mollusk species, Haliotis tuberculata, H. asinina, Chlamys farreri, Crassostrea gigas, and Argopecten irradians (Farcy et al 2007;Gao et al 2007Gao et al , 2008Gunter and Degnan 2007;Choi et al 2008).…”
Section: Introductionmentioning
confidence: 99%